ROLE OF ASPIRIN IN PREVENTING CARDIOVASCULAR DISEASE. A SCIENTIFIC REVIEW OF CLINICAL TRIALS. - Sultan Ghazi Ahmad Alsulaimani, Ahmed Abdu Sulaiman Bajafar, Samar Jamil Hamza Fadul, Saeedah Abdu Sulaiman Bajafar, Ahmad Waleed Malas, Yasser Ali Alharbi, Hassan Siddiq Omar Nahhas, Abdulaziz Mohammad Alghamdi; Ayman Ahmed Saleh Alghamdi, Basim Aref Almosafeh (Chelonian Research Foundation, 2022)
Aspirin therapy is widely acknowledged as an effective treatment for preventing cardiovascular events that occur after a first incident. Current guidelines recognize the use of aspirin in preventing cardiovascular events before they occur. This review provides an overview of the important trials involving the use of aspirin and their relevance to current guidelines. It also explores several aspects that can impact the effectiveness of aspirin therapy in preventing cardiovascular disease. We conducted a search on PubMed, covering the period from January 2016 to January 2022, to identify recent clinical studies and guidelines related to the use of aspirin for primary prevention of ASCVD. We limited the studies to randomized, controlled clinical trials. The available evidence strongly indicates that aspirin has a beneficial effect in preventing cardiovascular events in specific demographic groups, both for individuals who have already had such events (secondary prevention) and for those who have not yet experienced them (primary prevention). However, the way in which aspirin is currently being used in practice may not be ideal. As a cost-effective and uncomplicated preventive therapy for cardiovascular disease, the use of aspirin should be thoroughly evaluated in all adult patients at risk. Additional steps, such as patient education, are essential to guarantee its appropriate utilization. Keywords- Anticoagulant, Aspirin, Cardiovascular, Bleeding risk